DeepL Translate can be a scaffold to speaking fluency: Technology Acceptance Model (TAM) - Muhammad Chairil Imran; Mutmainnah Marzuki; Luana Sasabobe; Yuriatson Jubhari; Sujarwo Sujarwo (CV. Eureka Murakabi Abadi, 2025)
The numerous applications bring benefits to students; the fact that students spend more time using existing technology and demonstrate mastery of information technology allows instructors to motivate students who are unmotivated to speak. Lecturers have introduced DeepL Translate to improve students' speaking, while academics investigate the Technology Acceptance Model (TAM), which is designed to assess students' adoption of information systems. This study utilised a descriptive quantitative approach to examine students' reactions to the application of DeepL Translate in the educational process. Data were gathered by a standardised questionnaire featuring Likert-scale items that assessed perceived utility, convenience of use, and user satisfaction. The gathered replies were subsequently analysed by descriptive statistics, encompassing percentages and mean scores, to ascertain the overarching trends and patterns in the students' acceptance and experiences. The overall sample size is 150 students from the English education department at Universitas Islam Makassar and Megarezky University are used overall. The data gathered from the questionnaire reveal a favourable reception of DeepL Translate across diverse educational settings. This indicates that students had comfort and support from the utilisation of this translation technology, facilitating both comprehension of materials and translation text, while also aiding overall foreign language learning endeavours. Consequently, DeepL Translate can be regarded as an efficient and widely endorsed educational resource.